Cholesterol-Dependent Modulation of Stem Cell Biomechanics: Application to Adipogenesis - Sun, Shan (J Biomech Eng, 2019)
Cell mechanics has been shown to regulate stem cell differentiation. We have previously reported that altered cell stiffness of mesenchymal stem cells can delay or facilitate biochemically directed differentiation. One of the factors that can affect the cell stiffness is cholesterol. However, the effect of cholesterol on differentiation of human mesenchymal stem cells remains elusive. In this paper, we demonstrate that cholesterol is involved in the modulation of the cell stiffness and subsequent adipogenic differentiation. Rapid cytoskeletal actin reorganization was evident and correlated with the cell's Young's modulus measured using atomic force microscopy. In addition, the level of membrane-bound cholesterol was found to increase during adipogenic differentiation and inversely varied with the cell stiffness. Furthermore, cholesterol played a key role in the regulation of the cell morphology and biomechanics, suggesting its crucial involvement in mechanotransduction. To better understand the underlying mechanisms, we investigated the effect of cholesterol on the membrane–cytoskeleton linker proteins (ezrin and moesin). Cholesterol depletion was found to upregulate the ezrin expression which promoted cell spreading, increased Young's modulus, and hindered adipogenesis. In contrast, cholesterol enrichment increased the moesin expression, decreased Young's modulus, and induced cell rounding and facilitated adipogenesis. Taken together, cholesterol appears to regulate the stem cell mechanics and adipogenesis through the membrane-associated linker proteins.